Two Treatises of Philo of Alexandria : A Commentary on De Gigantibus and Quod Deus sit Immutabilis - Winston, David; Dillon, John (Book collections on Project MUSE., 2020)
"This is a detailed commentary on two paradigmatic books of the Jewish philosopher, Philo of Alexandria."--Provided by publisher